2001
DOI: 10.1016/s0042-6989(00)00267-4
|View full text |Cite
|
Sign up to set email alerts
|

Putting spatial attention on the map: timing and localization of stimulus selection processes in striate and extrastriate visual areas

Abstract: This study investigated the cortical mechanisms of visual-spatial attention in a task where subjects discriminated patterned targets in one visual field at a time. Functional magnetic imaging (fMRI) was used to localize attention-related changes in neural activity within specific retinotopic visual areas, while recordings of event-related brain potentials (ERPs) traced the time course of these changes. The earliest ERP components enhanced by attention occurred in the time range 70-130 ms post-stimulus onset, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
195
3
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(232 citation statements)
references
References 62 publications
32
195
3
1
Order By: Relevance
“…The backward progression of attentional effects from V4 to V1 is consistent with the findings of Mehta et al (24), who used a cross-modal attention design with a diffuse visual stimulus in monkeys, as well as the findings of Martinez et al (35) based on the timing of attentional effects on event-related potentials in humans. Other monkey studies have found smaller attentional effects in V1 than in V4 (3,4,6), although the latencies of attentional effects were not reported in those studies.…”
Section: Discussionsupporting
confidence: 88%
“…The backward progression of attentional effects from V4 to V1 is consistent with the findings of Mehta et al (24), who used a cross-modal attention design with a diffuse visual stimulus in monkeys, as well as the findings of Martinez et al (35) based on the timing of attentional effects on event-related potentials in humans. Other monkey studies have found smaller attentional effects in V1 than in V4 (3,4,6), although the latencies of attentional effects were not reported in those studies.…”
Section: Discussionsupporting
confidence: 88%
“…With a time range of 100-120 ms, this modulation arose soon (i.e., 27 ms) after the onset of the initial feedforward-driven activity in V1 and very rapidly (11 ms) after the onset of activity in extrastriate areas. Importantly, it appeared much earlier than attention-related recurrent activity modulations in V1, which have been found to arise not until after 150-250 ms after stimulus onset (2)(3)(4)(5)19). The considerable difference in the time course of awareness and attention-related modulations suggests that both represent distinct recurrent processing operations in V1.…”
Section: Correlates Of Successful Target Identification (Tm Trials)mentioning
confidence: 87%
“…One inherent technical difficulty of all retinotopic methods is that of attention and fixation: even though performance of retinotopic mapping seems to be in part independent from attention [35], the individual needs to be able to fixate throughout the 25 minute examination time. It should be noted, however, that one to two polar angle mapping scans are sufficient for the ROI definitions of V1 and…”
Section: Discussionmentioning
confidence: 99%